(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2025)
Question: What is the species composition and occurrence of Epicoccum fungi on crop seeds in Western Ukraine? Location: Ukraine. Materials and methods: culture methods combined with genetic marker analysis. Nomenclature: https://www.indexfungorum.org/ The genus Epicoccum belongs to the group of Phoma-like fungi and is characterized by unique morphological and cultural features. Its representatives are widespread saprotrophs and facultative endophytes frequently found on the seeds of agricultural crops. Due to considerable morphological variability and the presence of twin species, accurate identification of Epicoccum isolates requires the use of molecular-genetic methods. Such studies had not been conducted in Ukraine until now. The aim of this study was to clarify the species composition of Epicoccum fungi associated with seeds of wheat, barley, and soybean grown in the western regions of Ukraine, and to analyze their frequency of occurrence. The research began in 2019 at the V.N. Karazin Kharkiv National University but was interrupted by the onset of full-scale war. The investigation was resumed in 2023–2024 in the Research Department of Continental Farmers Group company in Ternopil region. Seed samples used in the study were collected from Ivano-Frankivsk, Lviv, Ternopil, and Khmelnytskyi regions. For iden-tification of the isolates, culture-based methods and sequencing of the internal transcribed spacer (ITS) region of ribosomal DNA were employed. The results showed that the vast majority of isolates belonged to Epicoccum nigrum sensu stricto. One isolate was identified as Epicoccum tobaicum (= E. layuense), marking the first confirmed report of this species in Ukraine. Its identification was verified at the labora-tory of Professor Pedro W. Crous (Westerdijk Fungal Biodiversity Institute, the Netherlands). It was established that in 2024, the average contamination level of wheat seeds with Epicoccum spp. was 2.7 %, and 2.3 % for soybean seeds, although in some samples these values reached up to 16.8 % and 12.3 %, respectively. The presence of Epicoccum spp. in seed samples may complicate phytosanitary assessments and lead to misdiagnosis of seedborne diseases such as Fusarium infections. The results of this study may help refine seed mycological testing protocols and enhance the accuracy of seed quality assessment.